The Effect of The Role of School Resources and School Performance on The Admission Strategy of New Students - Teddy Oswari; Siti Juariah (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
This study aims to describe the role of school resources and school performance in order to create a strategy in increasing the acceptance of new students at private junior high schools in Bekasi district. The research approach used is a quantitative approach with case studies. The research instrument is human and non-human resources in the school. Collecting data using questionnaires to respondents. Respondents consisted of elements of the education office, foundation organs, all school members and parents/guardians of students. The analysis technique uses Multiple Linear Regression with SPSS version 25. The conclusion is that the role of the principal, the role of the teacher/educator, the principal's performance and the teacher's performance have a significant effect in influencing the strategy of accepting new students at Barhari Private Junior High School, Bekasi Regency or in other words accept H1.